2001
DOI: 10.1046/j.1432-1327.2001.02074.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the PII–ATP complex

Abstract: P II is a signal transduction protein that is part of the cellular machinery used by many bacteria to regulate the activity of glutamine synthetase and the transcription of its gene. The structure of P II was solved using a hexagonal crystal form (form I). The more physiologically relevant form of P II is a complex with small molecule effectors. We describe the structure of P II with ATP obtained by analysis of two different crystal forms (forms II and III) that were obtained by co-crystallization of P II with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 29 publications
3
66
0
Order By: Relevance
“…An important difference between the ADP complex observed here and the E. coli GlnK-ATP (21) and E. coli GlnB-ATP (26) complexes is that in the latter cases the T-loop is disordered beyond residue G37. However, in our structure the T-loop is fully ordered, and we observe the two hydrogen bonds of the main-chain NH groups of residues R38 and Q39 with ␣-phosphate oxygens (Fig.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…An important difference between the ADP complex observed here and the E. coli GlnK-ATP (21) and E. coli GlnB-ATP (26) complexes is that in the latter cases the T-loop is disordered beyond residue G37. However, in our structure the T-loop is fully ordered, and we observe the two hydrogen bonds of the main-chain NH groups of residues R38 and Q39 with ␣-phosphate oxygens (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Thus, we observe an ADP-bound state of E. coli P II , with a stoichiometry of 3ADP:GlnK 3 . Previous studies have shown ATP can bind to this site in both E. coli GlnK (21) and GlnB (26). However, given the close contacts with neighboring amino acid main-chain and side-chain atoms all around the diphosphate moiety as verified through omit maps, we rule out that we are observing ATP with a disordered ␥-phosphate.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations